2012
DOI: 10.1371/journal.pone.0052310
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulated miR155 Reverses the Epithelial-mesenchymal Transition Induced by EGF and Increases Chemo-sensitivity to Cisplatin in Human Caski Cervical Cancer Cells

Abstract: The epithelial-mesenchymal transition (EMT) induced by EGF promotes cervical cancer progression; however, the mechanisms underlying the EGF-induced EMT remain unclear. In this study, we reported that miR155 overexpression suppressed EGF-induced EMT, decreased migration/invasion capacities, inhibited cell proliferation and increased the chemo-sensitivity to DDP in human Caski cervical cancer cells. Further, the overexpression of miR155 increased TP53 expression but reduced SMAD2, and CCND1 expression levels. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 22 publications
0
40
0
1
Order By: Relevance
“…EMT is a dynamic process that can be regulated and reversed by various factors, including miRNA (21). Alterations in cell morphology and function during the EMT process are accompanied by changes in protein expression profiles, including the loss of epithelial markers and the de novo expression of mesenchymal markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT is a dynamic process that can be regulated and reversed by various factors, including miRNA (21). Alterations in cell morphology and function during the EMT process are accompanied by changes in protein expression profiles, including the loss of epithelial markers and the de novo expression of mesenchymal markers.…”
Section: Discussionmentioning
confidence: 99%
“…However, silencing ANXA2 reversed the downregulation of E-cad and upregulation of N-cad that was induced by EGF treatment. In mesenchymal-like cells, downregulation of E-cadherin or upregulation of N-cad is characterized as the major hallmark responsible for the loss of cell-cell contacts in EMT events (21). E-cadherin, which is present in mature adherens junctions, is a pivotal molecule that maintains epithelial cell polarity.…”
mentioning
confidence: 99%
“…The over-expression of this miRNA leads to the down-regulation of SMAD2. In addition, miR-155 inhibits EGF-induced EMT in cervical cancer [38].…”
Section: Mirna and Emt In Cervical Cancermentioning
confidence: 99%
“…To this end, recent developments in miRNA studies have shown some promise. For example, miR-155 increases the chemo-sensitivity of cervical cells to cisplatin treatment by inhibiting EMT [38]. In addition, the downregulation of miR-29a, a tumour suppressive miRNA, is a frequent event in cervical SCC.…”
Section: Mirna and Emt In Cervical Cancermentioning
confidence: 99%
“…Varios miRNAs se clonaron a partir de tejido normal, líneas celulares, tejidos infectados con VPH y tejidos con cáncer de los cuales, miR15b, miR-16, miR-146a y miR-155 se encontraron sobre-expresados y miR-143, miR-145 y miR-128 infra-expresados 22,76,77 . Otro estudio mostró que miR-886-5p se sobre-expresa en los carcinomas de células escamosas de cuello uterino (SCC) en comparación con el tejido normal adyacente, mientras miR-302d, miR-346, miR-518b y miR-610 se infra-expresan 78 .…”
Section: Grupos De Mirnasunclassified